Analysis of the Psychometric Properties of the Perceived Social Support Scales in Older Adults - Shima Nazari; Mahshid Foroughan; Farahnaz Mohammadi Shahbolaghi; Maryam Rassouli; Leila Sadegh Moghadam; Akram Farhadi; Narjes Khatoon Sadeghi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: An important part of health status assessment of older adults is measurement of their perceived social support. Choosing a sound scale with good psychometrics properties is a prerequisite for proper assessment. The aim of this review article was to analyze the psychometric properties of perceived social support scales to help researchers become more familiar with positive and negative aspects of these instruments and select a more valid and appropriate one. Methods & Materials: A comprehensive search of databases of Medline, Google scholar, and Scopus was conducted, using the keywords related to design and process of psychometrics scales of perceived social support. In this regard, the articles published from 1970 until 2014 were collected. Then, the psychometric properties of the selected scales, including validity, reliability, responsiveness, and interpretability were assessed using the COSMIN comprehensive checklist. Results: Most of the scales had not reported a complete and desirable psychometrics properties. Some of them, despite of being developed for adult populations, lacked the capability for using in older adults (length of scale, length of questions, special questions). Conclusion: The results revealed that despite the lack of an appropriate scale for measurement of old adults perceived social support, the MOS is the only scale which can be recommended to gerontologists until now. However, a vital need is felt for developing an instrument based on cultural and social characteristics of different societies with acceptable psychometrics properties for measuring perceived social support in older adults.